Management of functional communication, swallowing, cough and related disorders: consensus recommendations for speech and language therapy. Issue 10 (1st July 2021) - Baker, Janet; Barnett, Caroline; Cavalli, Lesley; Dietrich, Maria; Dixon, Lorna; Duffy, Joseph R; Elias, Annie; Fraser, Diane E; Freeburn, Jennifer L; Gregory, Catherine; McKenzie, Kirsty; Miller, Nick; et al.
Abstract : Communication problems (eg, dysphonia, dysfluency and language and articulation disorders), swallowing disorders (dysphagia and globus), cough and upper airway symptoms, resulting from functional neurological disorder (FND), are commonly encountered by speech and language professionals. However, there are few descriptions in the literature of the most effective practical management approaches. This consensus document aims to provide recommendations for assessment and intervention that are relevant to both adults and young people. An international panel of speech and language professionals with expertise in FND were approached to take part. Participants responded individually by email to a set of key questions regarding best practice for assessment and interventions. Next, a video conference was held in which participants discussed and debated the answers to these key questions, aiming to achieve consensus on each issue. Drafts of the collated consensus recommendations were circulated until consensus was achieved. FND should be diagnosed on the basis of positive clinical features. Speech and language therapy for FND should address illness beliefs, self-directed attention and abnormal movement patterns through a process of education, symptomatic treatment and cognitive behavioural therapy within a supportive therapeutic environment. We provide specific examples of these strategies for different symptoms. Speech and language professionals have a key role in the management of people with communication and related symptoms of FND. It is intended that these expert recommendations serve as both a practical toolkit and a starting point for further research into evidence-based treatments.